Epidemiology of stroke: findings from a community-based survey in rural Bangladesh. (July 2018) - Saha, U.K.; Alam, M.B.; Rahman, A.K.M.F.; Hussain, A.H.M.E.; Mashreky, S.R.; Mandal, G.; Mohammad, Q.D.
Abstract: Objectives: This study was designed to determine the epidemiology of stroke in a rural population of Bangladesh. Study design: In a cross-sectional study, we surveyed stroke patients. Methods: The survey was conducted in a rural community of Bangladesh from January 2016 to June 2016. All community members 15 years and older in a surveillance system were included in this study. The Questionnaire for Verifying Stroke-Free Status was used to screen stroke cases at household level which were again examined by the neurologist for confirmatory diagnosis. Results: The prevalence of stroke was 1.96 (95% confidence interval [CI] 1.69–2.26) per 1000 population. The highest prevalence was 9.65 (95% CI 7.42–12.33) per 1000 population, identified among patients aged 65–79 years. Males had higher prevalence (2.38 per 1000 population) than females (1.55 per 1000 population). Of the 24% of patients who had radiological examination (magnetic resonance imaging and computed tomography scan) reports, 17.2% of stroke cases were ischemic, 4.8% were intracerebral, and about 1.1% were subarachnoid. The ratio of infarction to hemorrhage was 2.91. Approximately 67% of patients were diagnosed as hypertensive, and 37% of patients had elevated blood glucose level. While 15% of patients were found to be overweight or obese, 45% of patients had raised blood cholesterol level. More than 10% of patients reported that they had heart disease before the occurrence of stroke. About 40% of patients had the history of tobacco consumption. Conclusions: The prevalence of stroke is higher among elderly and male populations. A significant proportion of patients presented with hypertension and/or diabetes. Highlights: Stroke is a major public health problem in Bangladesh. Males and elderly people are the vulnerable population for stroke. Substantial proportion of stroke patients are living with raised blood pressure and raised blood glucose level.